Lycorine possesses notable anticancer potentials in on-small cell lung carcinoma cells via blocking Wnt/β-catenin signaling and epithelial-mesenchymal transition (EMT) - Yanfang, Sun; Sharopov, Farukh (Biochemical and biophysical research communications, 2018)
Lycorine, an natural isoquinoline alkaloid has reportedly that possesses multi-anticancer activity. However, to date, the anticancer feature of lycorine in non-small cell lung carcinoma (NSCLC) has still not fully been spelled out. The present study mainly focused on the molecular mechanism of lycorine against NSCLC in vitro and vivo. The results showed that lycorine evidently inhibited proliferation of A549 and H460 with IC50 values were 10.83 ± 1.14 μM and 12.35 ± 1.13 μM, while caused slight cytotoxicity in normal pulmonary epithelial Beas-2B cells, and arrested cell cycle in G0/G1 phase. Hoechst DNA-binding staining showed that typical characteristics of nuclear morphology apoptosis, AnnexinV-FITC/PI staining revealed the early-period apoptosis and the dissipation of mitochondrial membrane potential (Δψm) were also captured after lycorine treatment. Moreover, lycorine effectively repressed the Wnt/β-catenin signaling and reversed epithelial-mesenchymal transition (EMT). In addition, lycorine also intervened the caspase-mediated mitochondrial apoptosis pathway. Furthermore, A549/Luc tumor xenograft model was also corroborated that lycorine significantly suppressed the growth and metastasis of the lung tumor. These data highlight the significance of lycorine as potential anti-neoplastic agents to combat NSCLC.
Available online 7 November 2017
Gesehen am 19.06.2018